1997
DOI: 10.2190/ngdu-h73e-xmr3-tg5j
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Factor Structures of the Computer Attitude Scale

Abstract: Previous research regarding the popular Computer Attitude Scale (CAS) has indicated that the computer confidence and computer anxiety subscales measure the same trait. This study, utilizing data yielded from 208 educators, obtained estimates of the reliability of the four subscale version of the forty item CAS; provided detailed information regarding the factor patterns of the CAS subscales; and provided evidence about the differential validity of the CAS among four groups with differing intensity of computer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Wishart 63 found that increasing age was correlated with internal LOC. Nash and Moroz, 64 investigating the effects of positive attitudes towards computers, found no significant age effect. They do, however, report a correlation between age and experience, and that experience was related to 'computer liking'.…”
Section: Research Methods Survey Instrumentmentioning
confidence: 95%
“…Wishart 63 found that increasing age was correlated with internal LOC. Nash and Moroz, 64 investigating the effects of positive attitudes towards computers, found no significant age effect. They do, however, report a correlation between age and experience, and that experience was related to 'computer liking'.…”
Section: Research Methods Survey Instrumentmentioning
confidence: 95%
“…Previous research indicates that level of computer experience or perception of computer self-efficacy can affect subsequent user behavior (Brosnan 1998;Murphy, Coover, & Owen 1989). The authors chose the questions for this study after reviewing previous research on the Computer Aptitude Scale, assessing computer attitudes, computer anxiety-confidence, and computer liking (Loyd & Gressard 1984;Nash & Moroz 1997). These studies suggested that prior experience and level of perceived knowledge would affect an individual's level of frustration as well.…”
Section: Methodsmentioning
confidence: 99%
“…Hunt and Bohlin [63] found that the confidence subscale of Loyd and Gressard [62] was predicted by computer use for recreation and experience in word processing, programming and databases. Similarly, Nash and Moroz [64] found that Loyd and Gressard's [62] confidence subscale explained 32% of the variance in scores measuring intensity of computer usage. In addition, Zammit [65] not only found that non-users rated a lack of self-confidence among factors that hindered their use of computers but found a significant difference in selfconfidence between users and non-users.…”
Section: Perceived Usefulness and Perceived Ease Of Usementioning
confidence: 86%